Action observation plus motor imagery and somatosensory discrimination training are effective non-motor approaches to improve manual dexterity - Agnelli, Miriana; Libeccio, Benedetta; Frisoni, Maria Chiara; Bolzoni, Francesco; Temporiti, Federico; Gatti, Roberto (Journal of hand therapy, 2024)
Action observation plus motor imagery (AOMI) and somatosensory discrimination training (SSDT) represent sensory input-based approaches to train the motor system without necessarily asking subjects to perform active movements. To investigate AOMI and SSDT effects compared to no intervention on manual dexterity in healthy subjects. Randomized controlled study. Sixty healthy right-handed participants were randomized into AOMI, SSDT or Control (CTRL) groups. AOMI observed video-clips including right-hand dexterity tasks and concurrently performed motor imagery, SSDT performed surfaces recognition and 2-point distance discrimination tasks with the right hand, whereas CTRL underwent no intervention. A blinded physiotherapist assessed participants for manual dexterity using the Purdue Pegboard Test (Right hand-R, Left hand-L, Both hands-B, R+L+B and assembly tasks) at baseline (T0) and training end (T1). A mixed-design Analysis of Variance with Time as within-subject factor and Group as between-subject factor was used to investigate between-group differences over time. A Time by Group interaction and Time effect were found for R task, which increased from T0 to T1 in all groups with very large effect sizes for SSDT (d = 1.8, CI95 2.4-1.0, P < .001) and AOMI (d = 1.7, CI95 2.5-1.0, P < .001) and medium effect size for CTRL (d = 0.6, CI95 1.2-0.2, P < .001). Between-group post-hoc comparison for deltas (T1-T0) showed large effect size (d = 1.0, CI95 1.6-0.3, P = .003) in favor of SSDT and medium effect size (d = 0.7, CI95 1.4-0.1, P = .026) in favor of AOMI compared to CTRL. Time effects were found for L, B, R + L + B and assembly tasks (P < .001). AOMI and SSDT induced greater manual dexterity improvements than no intervention. These findings supported the role of visual and somatosensory stimuli in building a motor plan and enhancing the accuracy of hand movements. These non-motor approaches may enhance motor performance in job or hobbies requiring marked manual dexterity. •Input-based approaches are effective non-motor strategies to improve hand dexterity.•Action observation and motor imagery induce larger benefits than no intervention.•Somatosensory discrimination training induces larger benefits than no intervention.